Re-Adaptation of Traditional Malay House Concept as A Design Approach for Vertical Dwellings Malays - Misnat, Nordin; Surat, Mastor; M.S. Usman, Ismar; Binti Ahmad, Norfazillah (International Journal of Engineering and Technology, 2018)
Home is a basic need of human life and plays an important role in wellbeing human life. The quality of design should meet the needs and way of life as every human being deserves to enjoy it. Today's housing design failed to respond in meeting the needs of the occupants. The designs are now too much influenced from the west and contrary to the needs of the local design, especially the Malays. The space for the Malay Muslims is the reflection of the fulfilment of its way of life. The occupants are experiencing  multiple unfavourable housing issues. This paper highlight the housing issues and conditions on how certain issues of housing affordability affect societal wellbeing. The writing of this study will discuss the issues and problems of residential low and medium cost-of-modern design houses. Forty-five willing  respondents were randomly selected to answer questionnaires based on their willingness and the data were analysed using SPSS statistics to interpret these issues. The findings will be the basis for addressing the main issues and to proposed the application of the conceptual Malay heritage design in the design towards the creation of quality interior design dwelling.
Keywords: Traditional Malay House; Affordable House; Spatial Planning Design; Sustainability; Wellbeing